Regarding the assessment of the full life cycle cost of complex weapons systems and military equipment, taking into account the factor of its dynamics over time - Semenenko, Oleh; Semenenko, Liliia; Baranov, Sergii; Dobrovolskyi, Yuzef; Yarmolchyk, Maria; Tsymbal, Irina (Social Development and Security, 2023)
Purpose: The purpose of the article is to determine the peculiarities of taking into account the dynamic factor of the cost of complex samples of weapons and military equipment (aircraft, tank, ship) during the assessment of the full (combined) cost of their life cycle.Method: the main methods of research are methods of analysis, methods of military economic theory, and the method of comparison; formalization; abstraction and mathematical modeling.Findings: The main results of the article are: analysis of the main problematic issues regarding taking into account the dynamic factor of the cost of complex samples of weapons and military equipment during the assessment of the full (combined) cost of their life cycle; the proposed order (logic) of the formation of the indicator of the total cost of a complex sample (system) of OVT; proposed approach to take into account the influence of the dynamism factor on indicators of the total cost of complex samples of weapons and military equipment.Theoretical implications: the theoretical value of the study consists in determining the approach to the assessment of the full life cycle cost of complex weapons systems and military equipment, taking into account the factor of its dynamics over time.Paper type: theoretical, descriptive, practical, methodical.